Oral manifestation and its management in postmenopausal women: an integrated review - Sen, Suman; Sen, Sheuli; Dutta, Abhijit; Abhinandan, Abhinandan; Kumar, Vivek; Kumar Singh, Ajit (Menopause Review/Przegląd Menopauzalny, 2020)
Postmenopause is a phase of life which leads physical and emotional instability from multiple health related issues. Oral health in this stage of life is also compromised. Oral health has an impact on general wellbeing of the individual as oral cavity is commonly act as a mirror to general health. Menopause is phase in a woman’s life when menstrual cycles cease by reduced secretion of the ovarian hormones, such as estrogen and progesterone. This review article has emphasized on the diverse oral presentations of peri- and postmenopausal phase of women’s life. Practicing dental surgeons and general physician should be aware of the possible association of postmenopause and its various oral signs and symptoms in this midlife phase of women. It also focuses on its symptomatic management of various oral health issues. This article explains diverse oral conditions in detailed and their management. Stress causing anxiety and depression among this midlife phase of women can lead to alteration in immunity which can again lead to various oral conditions, like lichen planus, apthous ulcer that can cause burning sensation in oral mucosa and alter the food habit. By dealing with all this diverse condition, practicing oral physician can help to reduce and manage oral manifestation of postmenopausal phase of life.